(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper focuses on health seeking behavior among the working women in Nagapattinam Taluk of Tamil Nadu. India is on the path of becoming an economic superpower but its performance index in health component of human development, particularly that of women is not at all impressive. The typical female advantage in life expectancy is not seen in India. 75 percent of the working women are known to experience the ill effects of misery/general tension issue in contrast with ladies with lesser degrees of mental work environment requests. The main driver of this issue is related with the long working hours and exacting cutoff times. The study is based on Primary and secondary data. Data was collected by predesigned pretested semi-structured questionnaire. A pretested structured interview schedule was prepared to elicit information related to socio-demographic characteristics, health-seeking behaviour of the study participants. Hence the study made by the researcher with reference to Nagpattinam Taluk of Tamil Nadu. Totally 150 working women respondents were selected for that study. In conclusion, we can safely say that risk factors of lifestyle diseases like unhealthy food habits, physical inactivity, inappropriate body posture and disturbed biological clock should be avoided. Hence, working women’s safety and health issues at work need to be addressed and diagnosed at an early stage on priority. The government should take necessary and compulsory policies to improve the literacy rate and quality education as well as to provide adequate employment opportunities for women, which might explore positive impact on the women’s health concerns.